Analisis Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan (Penelitian Literature Review) - Bintang Fadillah; Fadjar Harimurti; Aris Eddy Sarwono (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This study aims to examine the effect of capital structure and profitability on firm value through literature studies. Firm value is an important indicator that reflects the performance and prospects of a company, one of which is measured by Price to Book Value (PBV). Capital structure is measured by Debt to Equity Ratio (DER), while profitability is measured by Return on Assets (ROA). The method used is descriptive qualitative by reviewing 12 related national journals. The results of the study show that the effect of capital structure on firm value is inconsistent; several studies show positive, negative, or insignificant effects. On the other hand, the effect of profitability tends to be more consistent, where most studies show a positive and significant relationship to firm value. This finding shows that profitability has a more dominant role in influencing firm value than capital structure. Therefore, increasing profitability through operational efficiency and appropriate business strategies needs to be the main focus of the company to increase value in the eyes of investors.